2013
DOI: 10.1016/j.jtrangeo.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Residential dissonance and mode choice

Abstract: Residential dissonance refers to the mismatch in land-use patterns between individuals' preferred residential neighbourhood type and the type of neighbourhood in which they currently reside. Current knowledge regarding the impact of residential dissonance is limited to short-term travel behaviours in urban vs. suburban, and rural vs. urban areas. Although the prevailing view is that dissonants adjust their orientation and lifestyle around their surrounding land use over time, empirical evidence is lacking to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 84 publications
6
46
0
Order By: Relevance
“…Policy interventions aimed at reducing the transport/land use impacts on the environment can be classified into push (e.g., travel behavioral changes by reducing the attractiveness of the car through higher taxes) and pull (e.g., travel behavioral changes by improving the attractiveness of public transport services by lowering fares and designing walkable roads) measures (Cools et al 2009;Kamruzzaman et al 2013). These measures can again be classified as soft or psychological (e.g., campaign, individualized travel planning, teleworking and car pooling) and hard/structural (i.e., modification in infrastructure or legislation) interventions (Department for Transport 2009; Graham-Rowe et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Policy interventions aimed at reducing the transport/land use impacts on the environment can be classified into push (e.g., travel behavioral changes by reducing the attractiveness of the car through higher taxes) and pull (e.g., travel behavioral changes by improving the attractiveness of public transport services by lowering fares and designing walkable roads) measures (Cools et al 2009;Kamruzzaman et al 2013). These measures can again be classified as soft or psychological (e.g., campaign, individualized travel planning, teleworking and car pooling) and hard/structural (i.e., modification in infrastructure or legislation) interventions (Department for Transport 2009; Graham-Rowe et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The big difference in mode share between TOD and TAD (e.g. auto mode shares in TAD and TOD are 68% and 25%, respectively) is observed in other studies (Renne, 2009;Renne and Ewing, 2013), sometimes less dramatically-approximately 70% (TOD) vs. 85% (non-TOD) (Kamruzzaman et al, 2013;Jeihani et al, 2013).…”
Section: Resultsmentioning
confidence: 55%
“…However, it is difficult to monitor changes in behaviour over time using this type of dataset because they are not collected from the same individuals over the periods. Consequently, panel surveys reflect the preferred option for modelling the dynamics of behaviour at the individual level (Kamruzzaman et al 2013). However, panel data are rarely available in transport research (Bhat and Guo 2007); and when and where they exist, their spatial and temporal coverage is often quite limited (Dargay 2007).…”
Section: Datamentioning
confidence: 99%
“…reduced income, loss of jobs, driving cessation, poorer health) have been identified as significant predictors of travel behaviour change. For example, Kamruzzaman et al (2013) have shown that individuals with better health are more likely to make a modal shift to AT. Life events (e.g.…”
Section: Introductionmentioning
confidence: 99%